Syntactic features of English noun phrases with reference to their Vietnamese equivalents / Trần Thị Mai Hương; NHDKH Assoc. Prof. Dr. Phan Văn Quế - Trần, Thị Mai Hương
This research aims to find out the similarities and differences between syntactic features of noun phrases in English and Vietnamese and give out some suggestions for teaching and translating noun phrases to Vietnamese learners. In the study I used descriptive research method and comparative method. Besides, the author uses survey questionnaires in form of a written test and the statistic method. The study explores the syntactic functions of English noun phrases and its equivalents in Vietnamese. It is hoped that the results of the study will partly contribute to the research of noun phrases. In addition, the study will bring in practical benefits to language teachers, translators, learners and people who are in favor of it.